Development Of Focusky-Based IPAS Learning Media To Improve Critical Thinking and Communication Skills - Muhammad Syahid; Indri Yani; Dadang Jaenudin (AFKARINA: Jurnal Pendidikan Agama Islam, 2026)
This study aimed to develop Focusky-based IPAS learning media to improve students’ critical thinking and communication skills on the topic “Plants as a Source of Life on Earth.” The research was conducted at MI Anwarul Hidayah involving fourth-grade elementary students. The study employed a Research and Development (R&D) method using the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation stages. The developed product was validated by material, media, and language experts, achieving scores of 80%, 91%, and 94%, respectively, with an average of 88%, indicating that the media was categorized as “feasible.” Furthermore, a limited trial involving 24 students showed a positive response rate of 97%, classified as “very feasible.” The results demonstrated that the use of Focusky-based IPAS learning media effectively enhanced students’ critical thinking skills, particularly in analyzing information, identifying cause-and-effect relationships, and drawing logical conclusions. In addition, students’ communication skills improved, as reflected in their ability to express ideas systematically, actively participate in discussions, and respond to peers’ opinions logically. Overall, the findings indicate that the developed media is effective and supports meaningful classroom learning